Improve The Microbiological Quality of Groundwater Around Bonoloyo Cemetery by Boiling - Elvina Sophia Ranti; Maurisa Yuant Khairani; Triastuti Rahayu (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Public cemeteries are considered to be a potential source of groundwater pathogen contamination. Many settlements in Indonesia are located near cemeteries and rely on groundwater for consumption. However, there is no information available on whether the simple method of boiling can improve the microbiological quality of groundwater around cemeteries. Therefore, this experimental study aimed to determine the effectiveness of boiling in improving the microbiological quality of groundwater around Bonoloyo Cemetery. The study had two treatments: groundwater without boiling (control) and groundwater that had been boiled. Samples were collected from two points (S1 and S2) inside the cemetery and three points (S3, S4, and S5) outside the cemetery. The microbiological quality of groundwater was analyzed using the MPN method for each treatment. Samples that produced gas in positive tubes were inoculated on eosin methylene blue (EMB) media. The results of the study showed that S1, S2, S3, and S5 had total coliform levels that exceeded the normal threshold for water. Fecal coliform was found in S3 and S5. However, after boiling, there was an average decrease in total coliforms in samples S1, S3, S4, and S5. There was also no growth of E. coli in samples S3 and S5. The decrease in MPN values ​​in the samples indicates that boiling can improve the microbiological quality of groundwater at cemetery Bonoloyo Surakarta.